2006
DOI: 10.1029/2005ja011273
|View full text |Cite
|
Sign up to set email alerts
|

Corotating solar wind streams and recurrent geomagnetic activity: A review

Abstract: [1] Solar wind fast streams emanating from solar coronal holes cause recurrent, moderate intensity geomagnetic activity at Earth. Intense magnetic field regions called Corotating Interaction Regions or CIRs are created by the interaction of fast streams with upstream slow streams. Because of the highly oscillatory nature of the GSM magnetic field z component within CIRs, the resultant magnetic storms are typically only weak to moderate in intensity. CIR-generated magnetic storm main phases of intensity Dst < À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
678
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 518 publications
(707 citation statements)
references
References 125 publications
28
678
0
1
Order By: Relevance
“…The electron response immediately following the HSS impact on 9 November shows the classic signatures noted by earlier observers [Kanekal, 2006;Tsurutani et al, 2006]. For example, examination of electron response from both MagEIS and REPT instruments show an expected energy-dependent differences in flux levels.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The electron response immediately following the HSS impact on 9 November shows the classic signatures noted by earlier observers [Kanekal, 2006;Tsurutani et al, 2006]. For example, examination of electron response from both MagEIS and REPT instruments show an expected energy-dependent differences in flux levels.…”
Section: Discussionmentioning
confidence: 60%
“…HSS, which are often associated with CIRs (corotating interaction regions) and CMEs both cause geomagnetic storms. The latter usually resulting in stronger storms (typically Dst < −100 nT) with a shorter recovery phase as compared to CIRs [Tsurutani et al, 2006]. While the electron response to IP drivers is a balance between energization and loss processes operating within the magnetosphere [Reeves et al, 2003], when there are increased fluxes associated with CIR-driven storms, they tend to occur at higher L shells, i.e., radial distances.…”
Section: Discussionmentioning
confidence: 99%
“…We made our own data archive including OMNI data and calculated (using OMNI data) additional parameters. In order to classify different SW types, we use method similar to ones which are based on comparison of relations of kinetic, thermal, and magnetic field energies in the studied SW streams and the corresponding relations in average solar wind and described in many papers (see reviews by Zurbuchen and Richardson [2006], Wimmer-Schweingruber et al [2006], Tsurutani et al [2006], and references therein). For this purpose we determine the following parameters: velocity V, density N, proton temperature T, module and components of IMF, proton thermal pressure NkT, proton plasma parameters (ratio of thermal and magnetic field pressures), ratio of measured temperature, and temperature estimated on the basis of average velocity-temperature relation T∕T exp , derivatives of them and compare them with standard threshold criteria which are present in Table 1 of paper by Yermolaev et al [2009].…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that the geomagnetic and solar activity correlation has decreased since the end of the 19th century, and the lag between them has increased. The variations of Rz and aa were in phase in the early period (solar cycles [11][12][13][14], and became out of phase in later periods (with a lag of 2 years in solar cycle 22) [4].…”
Section: Introductionmentioning
confidence: 99%
“…The geomagnetic activity has been found to be well correlated with the solar wind speed (v), the southward component (Bz) of the interplanetary magnetic field (IMF) and the product BzV 2 [5,9,10,11]. The solar sources of geomagnetic activity are generally thought to be of two categories [12,13]. One source, Coronal Mass Ejections (CMEs), has a frequency of occurrence that is in phase with the sunspot cycle while the second source, high-speed solar wind streams, is out of phase with the sunspot cycle.…”
Section: Introductionmentioning
confidence: 99%